LATGALES CERAMIC ENGRAVING WITH CO2 LASER - Petrovs, Aleksejs; Adijāns, Imants (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The paper discusses the need for a more accurate understanding of the results for certain laser parameters when engraving a material such as ceramics. For engraving the SUNTOP ST-CC9060 CO2 laser system was used and for measuring the OLYMPUS OLS5000 laser microscope was used. The objective of the experiments was to determine how engraving depends on the laser power and scanning speed.